2014
DOI: 10.1089/fpd.2013.1650
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks Attributed to Cheese: Differences Between Outbreaks Caused by Unpasteurized and Pasteurized Dairy Products, United States, 1998–2011

Abstract: Introduction The interstate commerce of unpasteurized fluid milk, also known as raw milk, is illegal in the United States, and intrastate sales are regulated independently by each state. However, U.S. Food and Drug Administration regulations allow the interstate sale of certain types of cheeses made from unpasteurized milk if specific aging requirements are met. We describe characteristics of these outbreaks, including differences between outbreaks linked to cheese made from pasteurized or unpasteurized milk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 22 publications
1
75
0
6
Order By: Relevance
“…This denotation is applied to most developed countries where incidence is low (USA: 0.40 cases per 1,000,000) [23]. Currently, the U.S. typically sees less than 100 reported cases per year, with most occurring in the south and southwest from illegally imported soft cheeses (unpasteurized) from Mexico [24]. However, in the U.S. true incidence has been estimated at five to 12 times greater, purely from foodborne illness [25].…”
Section: Global Presence Of Diseasementioning
confidence: 99%
“…This denotation is applied to most developed countries where incidence is low (USA: 0.40 cases per 1,000,000) [23]. Currently, the U.S. typically sees less than 100 reported cases per year, with most occurring in the south and southwest from illegally imported soft cheeses (unpasteurized) from Mexico [24]. However, in the U.S. true incidence has been estimated at five to 12 times greater, purely from foodborne illness [25].…”
Section: Global Presence Of Diseasementioning
confidence: 99%
“…In their study, Bianchi et al (2013) concluded that unpasteurized milk can be a vehicle for a variety of microorganisms (Listeria spp., Salmonella, and Campylobacter) and that outbreaks related to cheeses made with unpasteurized milk are also common (Gould et al, 2014). The development of a disease after consumption of contaminated dairy products made from raw milk depends on several factors, such as the pathogenicity of the bacteria strain, the number of ingested microorganisms, the physiological state of the microorganism, and the health condition of the consumer at the moment of ingestion (Verraes et al, 2015).…”
Section: Foodborne Disease Outbreaks Related To Dairy Productsmentioning
confidence: 99%
“…Surtos relacionados a doenças de origem alimentar decorrente do consumo de queijos, especialmente fabricados a partir de leite cru resultaram em um maior número de hospitalizações e foram atribuídos ao consumo de queijos fabricados ou comercializados de forma ilegal nos Estados Unidos (Gould et al, 2014). No Brasil, surtos envolvendo o consumo de queijos, especialmente os de fabricação caseira, ocorreram no Estado de Minas Gerais As principais causas desses surtos foram o uso de leite cru na fabricação de queijos, a pasteurização ineficiente, o uso de leite proveniente de animais com mastite, as contaminações cruzadas, as falhas no monitoramento da produção e a ineficiência dos procedimentos de higienização (Carmo et al, 2002, Perry, 2004.…”
Section: Introductionunclassified